Government Effectiveness, Political Stability And Economic Development: Evidence From Asean-5 Panel Data Model - Syam, Sri Fatmasari; Abdur-Rabb, Ahmad Faqhruddin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study analyzes the impact of government effectiveness and political stability on economic growth, as measured by GDP per capita, in five ASEAN countries: Indonesia, Malaysia, Singapore, Thailand, and the Philippines. Using panel data analysis from 2002 to 2022, the study explores how institutional factors and macroeconomic variables influence economic performance. Government effectiveness, which reflects the quality of public services, bureaucratic capacity, and policy credibility, and political stability, which indicates the absence of domestic conflict and uncertainty, are the two key variables tested. The study also incorporates macroeconomic indicators such as unemployment and inflation to control for economic conditions. The findings show that both government effectiveness and political stability have a significant positive impact on GDP per capita, while higher unemployment rates negatively affect economic growth. On the other hand, inflation has a relatively small positive effect on GDP per capita. These findings underscore the importance of strong institutions and political stability in fostering an environment conducive to sustainable economic development. This research contributes to the literature on governance and economic growth in Southeast Asia and provides insights for policy formulation aimed at enhancing institutional quality and maintaining political stability for long-term economic prosperity.